Abiraterone and Galeterone, Powerful Tools Against Prostate Cancer: Present and Perspective - Ivana Z. Kuzminac; Andrea R. Nikolić; Marina P. Savić; Jovana J. Ajduković (Pharmaceutics)
Due to the high prostate cancer incidence worldwide, the development of different methods of treatment continues to be a hot research topic. Since its first clinical application at the beginning of the 2010s, abiraterone in the form of prodrug abiraterone acetate continues to be the most used hormone derivative in the treatment of castration-resistant prostate cancer. This is the reason behind the publication of many scientific results regarding its synthesis, biological activity, metabolism, novel designed steroid derivatives based on its structure, etc. A similar steroid compound with a heterocycle in the C17 position, called galeterone, also designed to treat prostate cancer, continues to be in clinical studies, which provides further proof of the importance of these steroid derivatives. Besides prostate cancer treatment, abiraterone showed indications for possible clinical application in the treatment of breast, ovarian, lung, kidney, salivary gland, and adrenocortical cancer, congenital adrenal hyperplasia, Cushing’s syndrome, and COVID-19, while galeterone is investigated for its use against prostate, pancreatic, and breast cancer. Herein, we report a review comprising methods of synthesis, possible clinical applications, and mechanisms of action, as well as structures and bioactivities of derivatives of these two important steroids.